2003
DOI: 10.1016/s0002-9270(02)05934-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical severity score and the lower esophageal sphincter relaxation pressure in idiopathic achalasia

Abstract: Our study showed that a clinical symptom score can be an appropriate predictor of the LES relaxation pressure in patients with idiopathic achalasia before therapy. Further studies are needed to evaluate similar correlations after therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…8,10 TBE, HRM, and symptoms Review of prior literature regarding correlation of symptoms with TBE or HRM findings shows inconsistent results. 3,8,9,[13][14][15][16][17][18][19] Andersson and colleagues reported an inverse correlation between TBE width and postprandial chest pain (r = −0.44). 13 In a study by Yaghoobi and colleagues, active and passive regurgitation showed significant correlation with LES pressure.…”
Section: Principal Findingsmentioning
confidence: 99%
“…8,10 TBE, HRM, and symptoms Review of prior literature regarding correlation of symptoms with TBE or HRM findings shows inconsistent results. 3,8,9,[13][14][15][16][17][18][19] Andersson and colleagues reported an inverse correlation between TBE width and postprandial chest pain (r = −0.44). 13 In a study by Yaghoobi and colleagues, active and passive regurgitation showed significant correlation with LES pressure.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The severity of symptoms was evaluated on the basis of a symptom score previously reported by our group. 12,14 The symptom score was the sum of individual scores for five symptoms: dysphagia to solids, dysphagia to liquids, passive regurgitation, active regurgitation and chest pain. The severity of each of these symptoms was scored on a scale of 0-3 as depicted in Table 1.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Marked increase in the esophageal muscle thickness has also been described in a patient with dysphagia in whom the amplitude of contractions and peristalsis were normal, but the duration of contractions was prolonged [5].…”
Section: Discussionmentioning
confidence: 81%